Moore, Booker T. Washington, W.E.B. Du Bois, And The Struggle For Racial Uplift - Schulkin, Carl (Teaching History: A Journal of Methods, 2005)
Jacqueline Moore has succeeded admirably in achieving the stated objectives of her new history of the struggle for racial uplift in the United States at the turn of the twentieth century. She has produced a book that can be readily understood and enjoyed by "readers with little or no background on the subject." She has provided high school and college students and instructors at both levels with a detailed explanation of the Washington-Du Bois conflict, a topic "that most textbooks only briefly outline."